Increased Chemerin and Decreased Omentin-1 in Both Adipose Tissue and Plasma in Nascent Metabolic Syndrome - Jialal, Ishwarlal; Devaraj, Sridevi; Kaur, Harmeet; Adams-Huet, Beverley; Bremer, Andrew A. (The journal of clinical endocrinology and metabolism, 2013)
Context:Adipose tissue dysregulation causing aberrant adipokine secretion contributes toward the proinflammatory state of metabolic syndrome (MetS). However, there are scant data on the role of novel adipokines in MetS.Objective:The aim of this study was to determine the levels of circulating and adipose tissue-secreted adipokines, chemerin, omentin-1, resistin, and visfatin in nascent MetS patients without diabetes or cardiovascular disease and to determine their relation with features of MetS.Design and Setting:Subjects with MetS and gender- and age-matched controls were recruited after informed consent. Fasting blood samples and gluteal subcutaneous adipose tissue (SAT) biopsies were obtained.Main Outcome:SAT-secreted and plasma levels of chemerin, omentin-1, resistin, and visfatin were quantitated.Results:There was significantly higher circulating as well as SAT-released chemerin in nascent MetS compared to controls, which persisted after adjustment for body mass index, waist circumference, and age. Also, both SAT-released and plasma levels of omentin-1 were significantly lower in MetS compared to controls, and the significant differences persisted after adjustment for age, body mass index, or waist circumference. No significant differences were observed in the levels of circulating visfatin as well as SAT-secreted resistin and visfatin. Chemerin correlated significantly with high-sensitivity C-reactive protein, homeostasis model of assessment for insulin resistance, triglycerides, and blood pressure, and inversely with omentin and high-density lipoprotein cholesterol. Omentin correlated significantly with high-density lipoprotein cholesterol and inversely with glucose and triglycerides.Conclusions:We make the novel observation of abnormal circulating and gluteal SAT-secreted chemerin and omentin-1 levels in nascent MetS, which could confer a higher risk for diabetes and cardiovascular disease.